Phylogeny and Evolution of the Brown Algae. (3rd July 2020) - Bringloe, Trevor T.; Starko, Samuel; Wade, Rachael M.; Vieira, Christophe; Kawai, Hiroshi; De Clerck, Olivier; Cock, J. Mark; Coelho, Susana M.; Destombe, Christophe; Valero, Myriam; Neiva, João; Pearson, Gareth A.; et al.
Abstract: The brown algae (Phaeophyceae) are a group of multicellular heterokonts that are ubiquitous in today's oceans. Large brown algae from multiple orders are the foundation to temperate coastal ecosystems globally, a role that extends into arctic and tropical regions, providing services indirectly through increased coastal productivity and habitat provisioning, and directly as a source of food and commercially important extracts. Recent multi-locus and genome-scale analyses have revolutionized our understanding of the brown algal phylogeny, providing a robust framework to test evolutionary hypotheses and interpret genomic variation across diverse brown algal lineages. Here, we review recent developments in our understanding of brown algal evolution based on modern advances in phylogenetics and functional genomics. We begin by summarizing modern phylogenetic hypotheses, illuminating the timescales over which the various brown algal orders diversified. We then discuss key insights on our understanding of brown algal life cycle variation and sexual reproduction systems derived from modern genomic techniques. We also review brown algal speciation mechanisms and the associated biogeographic patterns that have emerged globally. We conclude our review by discussing promising avenues for future research opened by genomic datasets, directions that are expected to reveal critical insights into brown algal evolution in past, present, and future oceans.